Acquisition of transgenic salt‐tolerant upland rice based on genetic algorithm and its resistance. (3rd October 2018) - Sun, Yina; Zhu, Fanhe; Dai, Weimin
Summary: Genetic algorithm is a search algorithm with "survival + detection" iterative process. Genetic algorithm is applied to study the gene optimization of rice yield increase to achieve the effect of increasing yield. The eco‐agricultural industrialization in China is still in its infancy, which requires technological innovation and institutional innovation of large‐scale eco‐economic optimization. This paper is devoted to the design of "three type" industrialization technology system of ecological agriculture resource saving, environment clean type, economic security type, and so on, and the construction of the new model of pollution abatement and recycling; the application of the transgenic technology is the development direction of advanced breeding technology, and it is the 4 investments of reducing pesticide, fertilizer, irrigation water, and labor force and the major technical countermeasures to promote the comparative benefit of grain. Super Hybrid Rice is a very good material for the transgenic technology, and the application of the transgenic technology is beneficial for super hybrid Rice to realize super High‐yield potential in large‐scale industrialized planting.